Level of Ethics and Integrity: Case Studies of Malaysian Public Sector Organizations - Asmawati, Sajari; Hasnah, Haron; Ishak, Ismail (2017)
The purpose of this paper is to measure the level of ethics and integrity in the three different types of public sector entities i.e., state level (CSA), state statutory body (CSB) and federal statutory body (CSC). An explanatory case study method is used to collect the data whereby semi structured interviews, informal conversations, questionnaire and document reviews are conducted. The overall shows score of the level of ethics and integrity is more than 50 percent indicating that all organizations studied are serious in initiating proper integrity mechanism into their daily activities at work places to maintain the highest levels of transparency, integrity and professionalism. CSB shows the highest percentage of 70.85% compared to CSA (68.26%) and CSC (66.10%). Further in depth study is highly recommended to get more generalize results on the factors that influencing the level of ethics and integrity in Malaysian public sector organization